Analysis Of Factors Affecting Stock Price Movements In The Technology Sector On The Indonesia Stock Exchange - Putra, Eko sasongko; Miqdad, Muhammad; Wahyuni, Nining Ika (Jurnal Ekonomi, 2024)
The problem raised in this research is multifactoral stock price volatility in the Indonesian technology industry. This research aims to reveal these characteristics in order to provide a comprehensive understanding of changes in share prices. In this way, investors and stakeholders will be able to face the dynamics of the Indonesian technology sector stock market by making more informed and intelligent investment decisions. This research uses multiple regression analysis using a purposive sample of 29 technology-related companies with complete financial reports and IDX registration. Based on research findings, interest rates are the only important variable that influences stock price fluctuations, with a coefficient of determination of 38.9% for the model accuracy percentage.